Design and evaluation of an energy storage system for helicopters - Klumpner, Christian; Rashed, Mohamed (2018)
This paper presents the design and evaluation of an energy storage system (ESS) for helicopters with the aim to recover the kinetic energy in the rotor available after landing and to be able to control the 270V dc bus voltage during load disturbances. A study is conducted in order to identify the suitable mix of commercially available energy storage devices with the aim of obtaining the minimum weight, exploring also the possibility to implement a hybrid supercapacitor-battery system. On the converter side, commercially available Silicon and Silicon-Carbide devices have been evaluated to achieve also the smallest size/weight.